THE EFFECT OF IMPLEMENTING PHET SIMULATION BASED STUDENT WORKSHEETS TO IMPROVE STUDENT LEARNING OUTCOMES ON TEMPERATURE MATERIAL AND CALORIES - Mahyana, Mahyana; Husnizar, Husnizar; Nurmalina, Nurmalina (Department of Physics Education, Faculty of Teacher Training and Education, UNIVERSITAS MA, 2024)
This study aims to determine the influence of implementing PheT-based Worksheets (LKPD) on Physics learning outcomes of students on the subject of Temperature and Heat in SMA Aceh Singkil. The research employed a qualitative approach with a scientific approach. Data collection was conducted using PheT Simulation-based LKPD sheets, while learning outcomes were assessed using pretest and posttest examinations through a one-group pretest-posttest approach. Based on the research findings and data analysis, there is a significant influence of PHET Simulation-based LKPD on improving physics learning outcomes of students at SMA Negeri Suro Singkil on the subject of Temperature and Heat, with a calculated thitung of 2.32, while the critical ttabel is 1.70. Based on the hypothesis testing criteria, Ho is accepted if thitung<ttabel and rejected if thitung>ttabel Since the calculated t-value is greater Ho is rejected, and Ha is accepted. This indicates that the use of PHET Simulation-based LKPD has a significant influence on improving high school students' physics learning outcomes on the subject of Temperature and Heat.